DIVERSITY, DISTRIBUTION AND CONSERVATION STATUS OF SHARK SPECIES FROM THE WATERS OF LANGKAI ISLAND, SPERMONDE ARCHIPELAGO - Aidah Ambo Ala Husain; Andi Muhammad Subhan; Andi Iqbal Burhanuddin; Budimawan Budimawan; Ahmad Bahar (Jurnal Ilmu Kelautan SPERMONDE, 2026)
Sharks as top predators in marine waters have important role in balancing the ecosystem, however they were suffering from high overfishing fishery. The study was conducted to identify species composition and sex determination observed sharks as well as mapping their distribution, and to define interviewed by-catch sharks into their conservation status based on the IUCN Red List. This research was carried out in April 2021 in the adjacent waters of Langkai Island, Spermonde Archipelago. A survey method was carried out to gather fisheries data and biological aspects of catches in 11 trips, as well as conducting interviews as secondary data needs. There were 20 individuals of identified shark with a length range of 58-131 cm, and within composition of five species: Chiloscyllium punctatum (45%), Triaenodon obesus (25%), Carcharhinus melanopterus (20%), C. falciformis (5%), and C. sealei (5%). The female sharks composition was higher (65%) than male ones (35%). The observed sharks were fished in the adjacent water of Langkai Island within distances of 0.20-8.25 km to the southwest of the island. Meanwhile, there had been 12 species of by-catch sharks from the fishermen interviews, which were classified into conservation status of Near Threatened (58%), Vulnerable (17%), Endangered (17%), and Critically Endangered (8%).